THE DRUM AND THE HOE - Life and Lore of the Haitian People, by HAROLD COURLANDER, University of California Press, 1960. xvi + 371 pp., 90 photographs, 109 pp. of musical transcriptions. - Blacking, John (International Library of African Music, 1960)
pages: 78-79
Keywords: African Music